Survey of Heavy Metals Residue (Ni and Cr) in raw Tarom rice and evaluation of cooking methods effectson the concentrations of thesemetals: Survey of Heavy Metals Residue (Ni and Cr) in raw Tarom rice and evaluation of its cooking effects - Nasri Nasrabadi, Nafiseh; Shokrzadeh, Mohammad; Jalal Sadat, Seyyed Nastouh; Alizadeh Chepy , Maryam (International Pharmacy Acta, 2021)
Introduction: Consumption of food contaminated by heavy metals, especially nickel and chromium, cause adverse effects on human health, including impairment of renal function, met - hemoglobinemia, cirrhosis, and many other intoxication consequences. Since rice is one of the main meals of Iranian people, this project was conducted to determine the amount of contamination of nickel and chromium in rice , and to find how the cooking process may be effective on these elements. Materials and Methods: Five samples were collected randomly from five geographic regions of Qaemshahr (i.e., North, South, East, West, and Center). Residues of nickel and chromium in raw and cooked rice were determined by the flame atomic absorption spectrophotometer (FAAS). Statistical analyses were done by SPSS V.18 software, and the mean values of groups were comprised by ANOVA software. Results: The average values of nickel / chromium were 0.174 ±0.01 for raw rice and 0.036±000 for the rinsing water of cooked rice. The amount of these elements in the cooked rice by the “Virgo” cooking method was 0.12 ±0.0311 and for the “kateh” method (ordinary cooking of rice) was 0.142±0.035, respectively. Conclusion: The results indicated that the cooking processes of Virgo and Kateh methods had positive impacts on reducing the amount of nickel / chromium compared to the raw rice.